The Lives and Livelihoods of Syrian Refugees in the Middle East : Evidence from the 2015-16 Surveys of Syrian Refugees and Host Communities in Jordan, Lebanon, and Kurdistan, Iraq - Krishnan, Nandini; Russo Riva, Flavio; Sharma, Dhiraj; Vishwanath, Tara (World Bank, Washington, DC, 2020)
The Syrian crisis has led to rapid and large-scale population displacement. This paper has two main aims. (i) It documents the size and timing of the Syrian refugee influx into Jordan, Lebanon, and Kurdistan, characterizing the forced nature of displacement and exploring factors that influenced the decision to flee and subsequently move within the host country. (ii) The paper describes the daily living conditions of refugees after displacement, documenting vulnerability along several dimensions, such as housing access and quality, labor market attachment, and financial security. The data sources include the United Nations High Commissioner for Refugees' registration database and multi-country, multi-topic surveys conducted in 2015-16.